Transnational Encounters, Deep Maps and The Sixto Rodriguez Phenomena - Cristian, Réka M. (Acta Hispanica, 2020)
The text focuses on a series of transnational flows and polylocal agencies marking the art of the American folk musician and performer Sixto Rodriguez. After issuing two albums in the seventies, he was quickly forgotten in the USA but luckily not outside of it. His first album, Cold Fact (1970), became the unofficial anthem for the anti-apartheid movement in South Africa in the seventies and the performer was paradoxically ‘rediscovered’ due to a hoax with the help of enduring South-African, Botswanan, Zimbabwean, Australian and New Zealander fans and through the research of the Swedish-Algerian filmmaker Malik Bendjelloul, who made and directed Searching for Sugarman (2012), an Oscar-winning documentary film. The quest for Rodriguez’s global itineraries still goes on through his official webpage and the release of a book in 2015 with performer-activist Rodriguez becoming in the context of global discourses and Deep Maps strategy a transnational figure rather than just an American singer.